Application of Foot Massage Therapy Procedures Using Lavender Essential Oil on Clients With Hypertension in RT 001 RW 01 Baru Village, Pasar Rebo District, East Jakarta - Resmiati Resmiari; Nurhayati Dwi Handayani; Violita Violita; Risma Suciyatiningrum (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Hypertension is one of the main problems in the world of health in Indonesia and the world. According to WHO (2011) there are 1 billion people in the world suffer from hypertension and 2/3 of them are in developing countries. This condition requires pharmacological and nonpharmacological treatment. One of them, giving foot massage therapy using lavender essential oil. Objective: This study aims to determine the effectiveness of applying foot massage procedures using lavender essential oil on hypertensive clients. Methods: This study uses a qualitative design to describe in-depth information about the application of foot massage therapy procedures using lavender essential oil on clients who have hypertension. Result: Foot massage is done using lavender essential oil for 15-20 minutes 2 x 1 day. Although the nursing problems are the same, the end result is different. After 3 days of intervention, there was a decrease in blood pressure in Mr D from 150/90 mmHg to 120/80 mmHg with a scale of pain from 4 to 0. While in Mr. S from 170/100 mmHg to 150/90 mmHg with a scale of pain from 5 to 1. Mr. D has decreased blood pressure more optimally than Mr. S because you do therapy regularly. Conclusion: of the study is that foot massage therapy using lavender essential oil can reduce the value of blood pressure and the scale of pain. This therapy is effective if done routinely and client can take advantage of health facilities.